Efek Kurkumin terhadap Pertumbuhan dan Perkembangan Fetus Rattus norvegicus L. - Istriyati Istriyati (Universitas Atma Jaya Yogyakarta, 2009)
Curcumin which is isolated from Curcuma longa L. rhizome, has been used as a food additive, medicinal agent, cosmetic and fabric dye, whithout known its side effects. This research is to study the effects of curcumin on the structure of forelimb finger. Twenty virgin female rats, 2 month old, 150 g body weight were mated with fertile male rats. The present of vaginal plug or spermatozoa in the vagina were determined as the first day of pregnancy. Pregnant animals were devided into 4 groups of 5. Treatment were started from 10th to 17th day of pregnancy. The first 2 groups for control and vehicle only. Curcumin was dissolved in aquous 5% Tween 80. The second 2 groups were given curcumin at the dosage of 100 and 150 mg kg -1 bw. Rats were sacrificed at 18th day of pregnancy. Foetuses were dissected out, fixed in 10% formalin. Morphology of the foetuses were observed, forelimb were processed by paraffin method, and plantar paraffin section were made and used for histological observations and cell development of fingers. The results showed that curcumin at the dosage of 100 mg kg-1 body weight caused some foetuses dead, resorption of the embryo, hemorrhagi, unilateral phocomelia. Microscopical observations showed the treatment caused induced of nail formation, inhibition of indensity interdigity, and the increased of new blood vessel formation. It was concluded that the curcumin has no effect on the growth of foetuses. However it was affected the development of forelimb finger which is non dosage dependent.